Genetic Imprinting: Comparative Analysis Between Plants and Mammals (Plant Tissue Culture and Biotechnology, 2016)
Genetic imprinting: the parent of origin?specific biased expression of alleles is an important type of epigenetic gene regulation in flowering plants and mammals. All imprinted genes show either maternal ? or paternal?specific mono?allelic expression. Considering that plants and mammals shared a common ancestor more than one billion years ago, significant overlap and potentially equally significant differences in the genomic imprinting mechanisms in these two taxa are emerging. In plants, the imprinted genes are primarily imprinted in the ephemeral endosperm tissues of the seeds which do not contribute any genome to future generations, while in mammals, the imprinted genes are located in embryo, placenta, and the adult body. Though both kingdoms silence imprinted genes using DNA methylation, imprinted alleles in mammals are targeted for silencing while in plants preexisting methylation is specifically removed from the allele destined to be active in maternally expressed genes in the endosperm. It is now accepted that imprinting evolved in both taxa due to competition between parental genomes over resource allocation to offspring. Moreover, the distinct life cycle stages between the taxa may account for the different strategies used by plants and mammals to regulate parent?specific gene expression. The elucidation of the genetic basis and molecular mechanisms responsible for genetic imprinting have provided answers to various crucial questions arising in biological sciencesPlant Tissue Cult. & Biotech. 26(2): 267-284, 2016 (December)